Drivers of vaccine decision-making in South Africa: A discrete choice experiment. Issue 15 (3rd April 2019) - Verelst, Frederik; Kessels, Roselinde; Delva, Wim; Beutels, Philippe; Willem, Lander
Highlights: We measured vaccine preferences in South Africa with a discrete choice experiment. Vaccine effectiveness and population coverage are key in vaccine decision-making. Vaccine utility is also driven by burden of disease and vaccine accessibility. Social norms and peer influence dominate rather than free-riding behavior. Abstract: To increase vaccination coverage, it is essential to understand the vaccine decision-making process. High population coverage is required to obtain herd immunity and to protect vulnerable groups in terms of age (e.g. the very young) or health (e.g. immunodeficiency). Vaccine confidence and coverage in South Africa are relatively low, opening the window for sustained outbreaks of vaccine-preventable diseases in a country facing one of the most severe HIV epidemics in the world. To capture the vaccine-related decision-making process in South Africa, we performed a discrete choice experiment with 1200 participants in December 2017. We asked for their preferences with respect to (1) vaccine effectiveness, (2) vaccine-preventable burden of disease, (3) accessibility of the vaccine in terms of co-payment and prescription requirements, (4) frequency of mild vaccine-related side-effects, (5) population vaccination coverage and (6) local vaccination coverage. We distinguished between decision-making for vaccines administered to the participant, and for vaccines administered to their youngest child. We analyzed the data for each of these groups using a panel mixed logit model and found similar results for decisions to vaccinate oneself or one's child. Vaccine effectiveness was the most important attribute followed by population coverage and burden of disease. Local coverage and accessibility were also important determinants of vaccination behavior, but to a lesser extent. Regarding population and local coverage, we observed a positive effect on vaccine utility indicating the potential of peer influence. As such, social normative influence could be exploited to increase vaccination confidence and coverage. With respect to vaccine-preventable burden of the disease, the marginal utilities showed disease severity to be more important than frequency of disease. Policymakers and health care workers should stress the effectiveness of vaccines together with the severity of vaccine-preventable diseases.